The Implementation of the Project Citizen Learning Model in Civics Education Subjects as an Effort to Build Civic Skills - Shopia Amalia; Sapriya Sapriya (Journal of International Conference Proceedings (JICP), 2020)
Civic Education learning empiric-practically is a process to build citizen’s awareness in solving problems in the environment. One of the awareness formations to actively participate in solving problems can be undertaken through Project Citizen learning model. This research observes the learning model in Civic Education subject in building civic skills at Public Junior High School 3 in Majalengka. The research method was used a case study. Data was collected through interviews, observations, literatures review and documents then analyzed with data reduction technique, data presentation, and verified by triangulation technique and data collection technique. The findings showed that the development of civic skill which includes communication skills, critical thinking, collaboration, and creativity are gained by students through all the steps in Project Citizen learning model.